High levels of polyphosphate kinase affect not only endotoxin production but also acid tolerance of Bacillus thuringiensis - Doruk, Tugrul; Girgin Ersoy, Zeynep; Oncel, Mehmet Salim; Tunca Gedik, Sedef (Tubitak Scientific & Technological Research Council Turkey, 2016)
Inorganic phosphate is stored as a polyphosphate (polyP) polymer inside every living cell. This polymer is synthesized by the polyP kinase (PPK) enzyme using the terminal phosphate of ATP as substrate and it performs important functions in the cell. In this study, effects of high levels of PPK on Bacillus thuringiensis subsp. israelensis were analyzed. Recombinant Bti ppk, a PPK overproducer, was found to uptake more phosphate into the cell and produce a consistently higher amount of endotoxin than the wild type under culture conditions including a range of temperatures (25 degrees C, 30 degrees C, and 37 degrees C), pH values (pH 5, 6, 8, and 9), and carbon sources (maltose, mannitol, sucrose, and starch). Moreover, this strain was found to overexpress sigB, which might cause a significant increase in the acid tolerance of this microorganism. Spores of Bti ppk were found to be smaller compared to wild-type spores; however, bioassay experiments with third-instar wild Culex pipiens larvae proved that high toxicity is not the result of small spore size. This hypertoxic recombinant Bti strain is very useful for industrial applications, not only because it produces more endotoxin than the wild type under different culture conditions, but also because it is more acid-tolerant under the conditions tested.
Keywords: Polyphosphate kinase; ppk; Bacillus thuringiensis; endotoxin; bioinsecticide